Mobile Phones and Water Point Mapping - Kazadi, Joy; Kleemeier, Elizabeth (World Bank, Washington, DC, 2012)
Several software applications incorporate recent advances in information and communication technology (ICT) to improve information gathering about water points. Among these applications, FLOW (Field Level Operations Watch) is not able because it was developed specifically for water point mapping. With FLOW, enumerators use android phones to enter data about each water point, and take its picture and Global Positioning System (GPS) coordinates. The data can be analyzed and visualized using additional capabilities of FLOW. Another software option is EpiSurveyor. It is easy to use and the free on line version is adequate for most data collection needs. The data could then be imported into FLOW, which has better analysis and visualization capabilities, or into another specialized application such as SPSS or Tableau.